MARKETING MIX DALAM PEMASARAN PERGURUAN TINGGI - Hasan Muzaki (AmaNU: Jurnal Manajemen dan Ekonomi, 2022)
The sustainability of a college is determined by many factors. Among them is whether the college is known or not so that the community will entrust the education process of their children to the college. Various efforts to introduce the university can be done with the right marketing strategy. Marketing mix is ​​a strategy of strengthening from within, either in the form of services or the provision of supporting services (physical and non-physical). The marketing mix is ​​a unit of several elements which in its implementation are interrelated and mutually supportive. Its application in higher education marketing is carried out with careful planning and involves all the existing academic community. The application of the marketing mix is ​​the right strategy because this strategy is a strengthening strategy from within so that it can be planned and programmed according to the capabilities and conditions of the university.